Radiologic diagnostics of joint affection under Lyme mite borreliosis - V. D. Zavadovskaya; A. V. Lepyekhin; L. S. Yekimova; T. B. Perova; S. S. Yekimov (Бюллетень сибирской медицины)
The aim of investigation was a determination of ultrasonic and radioisotopic feautures of joint affection under Lyme mite borreliosis (LMB). There have been examined 84 patients by ultrasonography method and 24 patients by scintigraphy method. These patients’ diagnosis of Lyme mite borreliosis has been verified with the results of serological examinations. Changes of joint structures by arthrosonography results have been consisted of: effusion of migrating nature, joint capsule thickening, local synovial proliferation, hyaline cartilage thinning and ligamentous apparatus hardening. By radionuclide examination the greater quantity of affected joints has been revealed as compared to patient’s complaints and arthsonographic status, it has been confirmed by the further case monitoring. As a first stage of radiologic diagnostics algorithm of patients with joint affection under LMB it has been recommended the use of radionuclide examination that allowed to execute a topic diagnostics of affected joints. As a second stage it has been optimum to execute arthrosonography in order to evaluate the nature of joint affection.